TOWARDS AN INTEGRAL STUDY OF RELIGIOSITY ROOTED IN MIRCEA ELIADE'S NEW HUMANISM - PREDA, Alina (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Towards an Integral Study of Religiosity Rooted in Mircea Eliade's New Humanism. The present article advocates for the development and the implementation of a philosophy of religiosity informed by Mircea Eliade’s new humanism, Eugeniu Sperantia’s axiotropism, D. D. Roşca’s outlook on human existence and Aurel Codoban’s hermeneutic philosophy of religions. If such an integral study of religiosity were to be accommodated by a new educational paradigm, the resulting humanist pro-social education would protect society from underlying drivers of polarisation such as religious dogmatism and fundamentalism. REZUMAT. Noul umanism eliadesc, studiul interdisciplinar al religiozităţii şi educaţia umanistă pro-socială. Pornind de la noul umanism eliadesc pe baza căruia Aurel Codoban a construit o filosofie hermeneutică a religiilor, utilizând teoria valorilor propusă de Eugeniu Sperantia precum şi concepţia filosofică a lui D. D. Roşca privitoare la condiţia umană, articolul de faţă propune introducerea unui studiu interdisciplinar al religiozităţii într-o nouă paradigmă educaţională. Educaţia umanistă pro-socială rezultată ar proteja societatea de extrem de nociva polarizare cauzată de fundamentalismul religios. Cuvinte-cheie: religie, religiozitate, noul umanism eliadesc, filosofia religiilor, atitudini-valori, idealul uman